Use of instagram to improve verbal-linguistic intelligence and kinesthetic-body intelligence of low-class students through scientific approach in primary schools - Yuliyanto, Aan; Amalia, Dinda Mifta; Muqodas, Idat (Universitas PGRI Madiun, 2020)
Verbal-Linguistic Intelligence and Kinesthetic-Body Intelligence are important for students to have at an early age. The purpose of this study is to see improvement in Verbal-Linguistic and Kinesthetic-Body Intelligence through Instagram-assisted Scientific Approaches. The study used a pre-experimental method with one group pretest-posttest design on the thematic learning of my hobby topic. Determination of the sample by purposive sampling technique. Participants consisted of 15 male students and 12 female students in first-grade elementary school in Purwakarta Regency. Measurement through observation and documentation to observe and record the activities of students' verbal-linguistic and kinesthetic intelligence. Research shows an increase in Verbal-Linguistic and Kinesthetic-Body Intelligence is in the medium category with n-gain values of 0.59 and 0.56, and an increase in Verbal-Linguistic and Kinesthetic-Body Intelligence after learning with a more scientific-assisted Instagram approach significantly better than before being treated with sig. 0,000<0.05. The use of Instagram shows students enthusiastic about expressing their hobbies. Learning development should be able to accommodate a variety of student intelligence and utilize social media that serves to facilitate learning and assessment more interesting